2021
DOI: 10.3390/ijerph18115554
|View full text |Cite
|
Sign up to set email alerts
|

Green Exercise: Can Nature Video Benefit Isometric Exercise?

Abstract: Green exercise is the combination of physical activity and nature exposure, which has been associated with positive effects on psychophysiological health. This study aimed to investigate the effects of nature video viewing on isometric exercise and find a useful practice for green exercise in urban living. In the current study, 18 male subjects were recruited in a randomized crossover trial and underwent a sequence of wall squat exercises. The whole experiment contained three periods of baseline (before exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Green exercise is a concept of nature-based exercise referring to exercises carried out in natural environments, which aims for the combined health benefits of nature exposure and physical activities ( Mnich et al, 2019 ). Due to the known health and training benefits of green exercise, many attempts have been made to replicate green exercise via media, and evidence indicates that a simulated natural environment may help reduce perceived exertion and provide a smooth exercise experience ( Akers et al, 2012 ; Li et al, 2021b ). As a technology that creates a better sense of immersion, VR is reported to have positive effects on the presence and perceived environmental restorativeness during a simulated nature walk, which is equivalent to the actual nature walk counterpart ( Calogiuri et al, 2017 ).…”
Section: Direction For Future Studymentioning
confidence: 99%
“…Green exercise is a concept of nature-based exercise referring to exercises carried out in natural environments, which aims for the combined health benefits of nature exposure and physical activities ( Mnich et al, 2019 ). Due to the known health and training benefits of green exercise, many attempts have been made to replicate green exercise via media, and evidence indicates that a simulated natural environment may help reduce perceived exertion and provide a smooth exercise experience ( Akers et al, 2012 ; Li et al, 2021b ). As a technology that creates a better sense of immersion, VR is reported to have positive effects on the presence and perceived environmental restorativeness during a simulated nature walk, which is equivalent to the actual nature walk counterpart ( Calogiuri et al, 2017 ).…”
Section: Direction For Future Studymentioning
confidence: 99%
“…Briki and Majed ( 79 ) revealed that walking for 20 min in a green environment induced a significant reduction in HR values. Li et al ( 80 ) also found that nature videos could buffer HR acceleration. In the current study, participants had to lie in bed for their treatment, which restricted their movement.…”
Section: Resultsmentioning
confidence: 98%